Penerapan Aspek Keberfungsian Sosial Levin Sebagai Instrumen Asesmen di Panti Lansia Bojongbata Pemalang - Wina Nurdini Kodaruddin; Sri Sulastri; Hery Wibowo (Sospol : Jurnal Sosial Politik, 2020)
AbstractBased on Central Java Governor Regulation No. 31/2018, the Bojongbata Nursing Home used to providing social services for the elderly. Unfortunately, Bojongbata Nursing Home does not have a special instrument for assessing the elderly's social function. The social function assessment usually used maps of social network and list of questions related to the elderly social relationships. However, this instrument has not been able to thoroughly explore the conditions, problems and needs of the elderly. In fact, an in-depth assessment of social functioning affects the determination of appropriate interventions and helps social workers analyze the conditions and service needs of the elderly. This study aims to identify the social functioning of the elderly through the aspects of Social Resources, Social Activities, Social Networking, Social Support, and Social Role and Role Functioning. This study analyzed several elderly informants with the aim of identifying their social functioning based on potential and non-potential groups. This is done to find differences in the conditions and needs of the two. The results of this study indicate that Levin assessment theory can describe the social functioning of the elderly. There is a relationship between aspects in realizing the better social functioning of the elderly. Elderly who can make good use of social resources and have adequate social activities have a wider and stronger social network. This social network can provide the social support needed by the elderly in carrying out their social roles properly.